2012
DOI: 10.1177/1088357612460572
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Picture Activity Schedule for Students With Intellectual Disability to Complete a Sequence of Tasks Following Verbal Directions

Abstract: We investigated instruction of independent creation of picture activity schedules (PASs) and how four middle school students with intellectual disability used them to complete tasks independently. A withdrawal design (A-BC-B-A-B) was used to evaluate whether the intervention had an effect on the dependent variable and to test for generalization to a community setting in a pre/post format. After instruction on the PAS, participants learned to self-manage a strategy that served as a reminder for the tasks they n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 10 publications
(10 reference statements)
0
38
0
Order By: Relevance
“…We retained articles that met inclusion criteria for further analysis. The comprehensive list included one of the 15 articles reviewed by Knight et al (2015; that is, Duttlinger, Ayres, Bevill-Davis, & Douglas, 2013 was the only study found to include participants with both ASD and ID). All articles used single-case research designs to evaluate effects of VAS.…”
Section: Methodsmentioning
confidence: 99%
“…We retained articles that met inclusion criteria for further analysis. The comprehensive list included one of the 15 articles reviewed by Knight et al (2015; that is, Duttlinger, Ayres, Bevill-Davis, & Douglas, 2013 was the only study found to include participants with both ASD and ID). All articles used single-case research designs to evaluate effects of VAS.…”
Section: Methodsmentioning
confidence: 99%
“…Each day people create their own SI materials to complete individual tasks (e.g., write down recipes, print out driving directions) and series of tasks (e.g., write down to-do list, input meetings and dates into electronic calendars). Duttlinger et al (2012) used least-to-most promoting to teach four middle school students, one with ASD, to create their own picture to-do list. As the teacher explained three to five tasks that needed completion, students placed corresponding BoardMaker pictures onto a strip of paper affixed with Velcro.…”
Section: Self-instructionmentioning
confidence: 99%
“…However, despite their popularity for a wide range of students and their theoretically predicted effectiveness, there are surprisingly few empirical studies of the use of visual schedules. A number of studies have explored the use of visual supports with children with Autism Spectrum Disorder (ASD) (e.g., Dettmer et al., ) or more broadly with students with a range of mild intellectual disabilities (e.g., Duttlinger et al., ). However, a review of the literature on visual activity schedules against criteria for evidence‐based practice (Knight, Sartini and Spriggs, ) concluded that there is a need for more research into the impact of visual schedules for both academic and daily living activities for children with ASD.…”
Section: Introductionmentioning
confidence: 99%